In vitro comparison of peracetic acid and autoclave sterilization in the corrosion of orthodontic pliers: a pilot study - Livia Kelly Ferraz NUNES; Érika Lopes CARNEIRO; Nathalia Barbosa PALOMARES; Lilian SENNA; Helio SAMPAIO-FILHO; José Augusto Mendes MIGUEL (Dental Press Editora, 2021)
ABSTRACT Introduction: The most currently recommended method for sterilization of orthodontic pliers is the autoclave, while peracetic acid has also been shown to be effective in the chemical sterilization process. Objective: This study sought to compare the corrosive effects of peracetic acid and autoclave sterilization process of orthodontic pliers. Methods: Four active tungsten carbide (WC) stainless steel tie-cutting pliers from the manufacturers Quinelato (Rio Claro, SP, Brazil) and ICE (Cajamar, SP, Brazil) were selected. The active ends of the pliers were sectioned, and six active tips were obtained and distributed into the following groups: 1) control group (no sterilization); 2) AC group (two active pliers tips submitted to 100 autoclave sterilization cycles); and 3) AP group (two active pliers tips submitted to 100 cycles of sterilization by immersion in 2% peracetic acid solution for 30 minutes). Results: Chemical analysis using X-ray dispersive energy spectroscopy showed that after autoclave sterilization, only the ICE pliers presented oxidation corrosion (Δ[O] = +24.5%; Δ[Fe] = +5.8%; Δ[WC] = -1.9%). In comparison, following peracetic acid sterilization, both manufacturers ICE (Δ[O] = +1.8%; Δ[Fe] = +18.0%; Δ[WC] = -1.1%) and Quinelato (Δ[O] = +5.3%; Δ[Fe] = -10.4%; Δ[WC] = -15.2%) showed corrosion. The morphological analysis revealed that peracetic acid caused a pitting and localized corrosion in both brands, while the autoclave caused uniform surface corrosion on the ICE pliers. Conclusion: Autoclave application was the sterilization method that generated less corrosive damage to the orthodontic cutting pliers, when compared to the immersion in 2% peracetic acid.